Under threes' play with tablets. (September 2021) - Marsh, Jackie; Lahmar, Jamal; Plowman, Lydia; Yamada-Rice, Dylan; Bishop, Julia; Scott, Fiona
This paper outlines the findings from a study that examined the tablet and app use of children aged from birth to three. The aim of the study was to examine how far use of tablets and apps promoted play and creativity. A total of 954 UK parents of children aged from birth to three who had access to a tablet in the home completed an online survey that explored the children's use of apps. Ethnographic case studies of four children aged from birth to three were undertaken in homes in order to explore in greater depth issues that emerged in the survey. The paper reports on the way in which the use of tablets promoted play and creativity across cognitive, physical social and cultural domains. The implications for policy and research are outlined.